Reconsidering S100B: Why it is time to abandon its use in detecting disease recurrence in stage III melanoma patients - Jansen, M.R.; Caini, S.; Stanganelli, I.; Been, L.B.; van Leeuwen, B.L. (European journal of surgical oncology, 2024)
Especially in the era of successful systemic therapy, there is an urgent need to detect early disease recurrence in stage III melanoma patients. This study investigates if serum S100 calcium-binding protein B (S100B) can detect disease recurrence in stage III melanoma patients. A retrospective cohort study was conducted at the University Medical Center Groningen (UMCG). Adult AJCC 8th stage III melanoma patients in whom serum S100B was measured as part of follow-up from January 2010 until April 2023 were included. The association between serum S100B and disease recurrence was evaluated using standard definitions for sensitivity and positive predictive value (PPV). Overall, 147 patients were included (mean age was 60.4 years, 53.1 % were female). Most patients were classified as stage IIIB (39, 26.5 %) and IIIC (73, 49.7 %). During median follow-up of 56 months, 69 (46.9 %) patients experienced disease recurrence. Seventeen out of 18 patients with elevated serum S100B (≥0.15 μg/L) experienced disease recurrence (PPV of 94.4 %). However, 52 out of 69 patients with disease recurrence had normal serum S100B (sensitivity of 24.6 %). Eight out of 17 (47.1 %) patients were asymptomatic (P = 0.608), twelve (70.6 %) patients had at least four distant metastases (P < 0.001). The clinical value of serum S100B to detect disease recurrence in stage III melanoma patients is negligible since only one out of four patients with disease recurrence have elevated serum S100B. Furthermore, half of stage III melanoma patients with elevated S100B experienced symptoms, and most patients already have multiple distant metastases.